Evaluation of the need for routine feeding jejunostomy for enteral nutrition after esophagectomy - Akiyama, Yuji; Iwaya, Takeshi; Endo, Fumitaka; Nikai, Haruka; Sato, Kei; Baba, Shigeaki; Chiba, Takehiro; Kimura, Toshimoto; Takahara, Takeshi; Nitta, Hiroyuki; Otsuka, Koki; Mizuno, Masaru; et al. (Journal of Thoracic Disease, 2018)
Background: Previous studies have shown that enteral nutrition (EN) helps reduce severe postoperative complications after esophagectomy. However, the incidence of jejunostomy-related complications is approximately 30%. We evaluated the operative outcomes in patients who did not receive EN via feeding jejunostomy after esophagectomy. Methods: We retrospectively reviewed 76 consecutive patients with esophageal cancer who received radical esophagectomy. Operative outcomes were compared between 33 patients who received postoperative EN via feeding jejunostomy (group A; from May 2014 to September 2015) and 43 patients who did not receive EN via feeding jejunostomy (group B; from September 2015 to December 2017). Results: The American Society of Anesthesiologists performance status score of the patients in group B was significantly higher than that of patients in group A (P=0.002). The postoperative morbidity rate was comparable between the two groups (group A, 30.3% vs. group B, 44.2%, P=0.217). No significant between-group differences were observed in the incidence of infectious complications, postoperative hospital stay, readmission within 30 days after discharge, or pneumonia after discharge within 6 months. The incidence of bowel obstruction was significantly higher in group A than in group B (group A, 9.1% vs. group B, 0%, P=0.044). Two patients in group B required nutritional support via total parenteral nutrition due to bilateral vocal cord palsy or pneumonia. Conclusions: Jejunostomy-related bowel obstruction in the patients with feeding jejunostomy was significantly higher than that in the patients without jejunostomy. There was no increase in postoperative complications (including pneumonia) in the patients who did not receive EN via feeding jejunostomy. Our results suggest that routine feeding jejunostomy may not be necessary for all patients undergoing esophagectomy.